The Urgency of Regulations on Waste Management in Indonesia - Esther Evelyn Simamora; Alfin Junuudhizbulloh (Universitas Negeri Semarang in collaboration with Ikatan Penulis Mahasiswa Hukum Indonesia, 2023)
ndonesia already has Law No. 18 of 2008 on Waste Management and its derivative regulations. However, the condition and need for waste management regulations continues to grow so the regulation is currently not in accordance with the development of waste management needs in Indonesia. In various Final Processing Sites (Tempat Pemrosesan Akhir), there has been some erosion due to being unable to accommodate existing garbage. The purpose of this research is to analyze the shortcomings of existing regulations and provide revised suggestions to the regulations. This research method uses normative research methods. The result of the analysis is that the regulation on waste management that currently exists is not comprehensive enough to regulate waste management. Waste management guidelines are technically submitted to the Regional Regulations causing uneven regulations and the implementation of these regulations is also inadequate. In Singapore, the waste management process is handled by the National Environment Agency and has the full support from the Government. The waste management process in Singapore is done by collecting waste with a special truck and then recycling and burning with an integrated system. Based on those problems, the laws and regulations related to waste management must be changed. In the preparation of the revision, Indonesia needs to learn from various other countries that already have a good system, such as Singapore. This is because the existing rules have not been able to regulate the entire waste management process. This rule needs to be prepared starting from the smallest scope, namely the scope of households, then from garbage carriers in the village scope, to the management at the Final Processing Site (TPA). The existence of regional autonomy to set their own waste management rules is not wrong. However, it is necessary to add compelling rules in the management that apply nationally.